PERBANDINGAN KEAKURATAN CAPITAL ASSETS PRICING MODEL (CAPM) DAN ARBITRAGE PRICING THEORY (APT) DALAM MENENTUKAN PILIHAN BERINVESTASI PADA SAHAM JAKARTA ISLAMIC INDEX (JII) - Safitri, Ervita; Utami, Dinarossi; Intan Sari, Putri (Jurnal Ilmu Manajemen, 2018)
The formulation of the problem in this study was how the accuracy of the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) in Determining the Choice of Investing in the Jakarta Islamic Index (JII). The objective of this study was to find out the differences of the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) in Determining the Choice of Investing in the Jakarta Islamic Index (JII). There were two balance methods that are still used as the approach material for accuracy in predicting expected return. The two models were the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT). In predicting CAPM company stock returns using risk-free return asset factors, market returns and beta while APT uses macroeconomic factors, namely interest rates, inflation, exchange rates and the money supply. The population in this study was 68 company shares after passing the purposive sampling stage, the sample of this study consisted of 27 monthly company shares that were registered continuously in the period 2010 - 2017. The data used in this study were secondary data with the data collection technique was documentation. The analysis technique used is independent sample t-test. The results of this study indicate that the CAPM method is more accurate than APT in determining the choice of investing in JII shares and there was no significant difference in accuracy between the CAPM and APT methods in determining the choice of investing in JII shares.